Application of DC-DC Converter in Sensor and MEMS Device Integration and Packaging. (22nd September 2022) - Wang, Shifeng; Ding, Xueyong; Tan, Qingji
Abstract : DC-DC (direct current controlled direct current) converter is the core control circuit in the field of power electronics technology. Based on the theory of sensors and MEMS (microelectromechanical systems), this paper constructs a DC-DC converter device integration and packaging model and proposes an enhanced current equalization technology with offset correction function suitable for two-phase DC-DC converters. Aiming at the generation mechanism of the output ripple of the two-phase DC-DC converter, the model adopts the ripple elimination technology based on the interleaved synchronous clock and the self-calibration interleaved time generator, so that each phase of the converter is accurately staggered within the full-load range, and the problem of output ripple amplitude is solved. During the simulation process, a high-performance two-phase DC-DC converter chip is designed and implemented, which includes an adaptive on-time control logic based on ripple feedback, a self-calibrating zero-current turn-off circuit, and a robust power switch transistor drive logic. The experimental results show that the full-load current of the chip reaches 6A, the peak efficiency is 91%, the phase-to-phase current error is <0.6%, and the output ripple is <9 mV. In the 90.265 V AC input, 0-10 W load range, the output voltage error is less than 0.96%, when the load is switched between no-load and full-load, and the system response speed is less than 200 ps, which effectively improves the overall performance of the DC-DC converter.